Predictive Validity of Minnesota Multiphasic Personality Inventory-2-Restructured Form Scale Scores in an Intimate Partner Violence Intervention Program - Whitman, Megan R. (Criminal justice and behavior, 2020)
Intimate partner violence intervention programs (IPVIPs) are intended to rehabilitate individuals charged with intimate partner violence (IPV) offenses, but these programs evidence high rates of treatment dismissal and recidivism. Applying the risk-needs-responsivity framework to improve IPVIP effectiveness has been suggested, and the Minnesota Multiphasic Personality Inventory-2-Restructured Form (MMPI-2-RF) may be used to inform risk estimates in this context. Past research has evaluated MMPI-2-RF Restructured Clinical scale scores in an IPVIP setting, but the remaining MMPI-2-RF substantive scales have yet to be evaluated. We tested the predictive validity of conceptually relevant MMPI-2-RF Higher-Order, Specific Problems, and Personality Psychopathology Five scale scores among a large sample of men who were court-mandated to treatment. Hierarchical logistic regression analyses indicated that several MMPI-2-RF scores incremented predictions of treatment dismissal and various recidivism variables beyond intake variables. Relative risk ratio analyses demonstrated promising utility of the measure in IPVIP settings.